Meridional circulation dynamics from 3D magnetohydrodynamic global solar convection - Passos, Dario (2018)
The form of solar meridional circulation is a very important ingredient for mean field flux transport dynamo models. However, a shroud of mystery still surrounds this large-scale flow, given that its measurement using current helioseismic techniques is challenging. In this work, we use results from three-dimensional global simulations of solar convection to infer the dynamical behavior of the established meridional circulation. We make a direct comparison between the meridional circulation that arises in these simulations and the latest observations. Based on our results, we argue that there should be an equatorward flow at the base of the convection zone at mid-latitudes, below the current maximum depth helioseismic measures can probe (0.75 R-circle dot). We also provide physical arguments to justify this behavior. The simulations indicate that the meridional circulation undergoes substantial changes in morphology as the magnetic cycle unfolds. We close by discussing the importance of these dynamical changes for current methods of observation which involve long averaging periods of helioseismic data. Also noteworthy is the fact that these topological changes indicate a rich interaction between magnetic fields and plasma flows, which challenges the ubiquitous kinematic approach used in the vast majority of mean field dynamo simulations.